Three dimensional convective flow of Sutterby nanofluid with activation energy - Muhammad Azam; Waqar Azeem Khan; Manoj Kumar Nayak; Abdul Majeed (Case Studies in Thermal Engineering, 2023)
Character of activation energy and nanofluids has a prominent significance in the field of oil reservoir, chemical engineering, geothermal engineering, heat exchanger, food processing, heat and mass transportation and cooling devices. The aim of current study is to present the mathematical modeling and numerical solutions of three dimensional flow of Sutterby nanofluid past a bidirectional moving surface under the influences of mixed convection, binary chemical reactions, viscous dissipation and activation energy. Boundary layer theory is abduced to model the physical problem in the form of partial differential equations. The obtained partial differential system is metamorphosed into ordinary differential system by operating appropriate conversion. Fehlberg Runge Kutta scheme is applied to derive the numerical simulations of reduced non-dimensional differential model. It is gripping to explore that fluid velocities f′(η) and g′(η) have opposite behavior due to the enrichment of Sutterby fluid parameter β₁. Additionally, higher approximation of chemical reaction parameter and activation energy parameter has reverse trends on nanoparticle concentration.